Non-Premixed Combustion Simulation with Variation of Swirl Burner Slope using Turbulence Modeling K-ɛ - R D Issafira; W Wijayanti; L Edahwati; W D Lestari; W Saputro; A K Faizin; N Adyono; T P Sari (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2021)
Combustion is a very complex matter. Therefore, we need to know the phenomenon that occur in combustion apart from the temperature distribution. This research uses quasi-research. The background in using quasi-experimental is because it has advantages in data collection. Moreover, the phenomena that occur in more detailed research by means of a numerical approach could also be observed. This research was conducted with an approach (simulation) of diffusion combustion using methane (CH4) fuel and air containing 29% oxygen (O2), 71% nitrogen (N2) and the addition of swirl in the air ducts. k-ɛ turbulence modeling was aaplied in this somulation. This variation of the fuel velocities are 3 m/s, 5 m/s, 7 m/s, where the air velocity was varied for 3 m/s, 5 m/s, 7m/s. In this simulation, room pressure of 1 atm was applied for the surrounding. The results showed that, the greater the angle of inclination of the swirl burner, the shorter the flame. And on the variation of fuel velocity, we get the result that the higher fuel velocity, increase fire height; however, the temperature of the fire height will decrease.